Analisis Faktor-Faktor yang Memengaruhi Kesempatan Kerja di 20 Provinsi dengan Penduduk Terpadat Tahun 2017–2024 - Dwi Utami Khoirunisa; Laela Indah Rahmah; Lisma Amalia; Melva Firdhian Nabillah; Mochamad Fakhri Fernanda (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study investigates the influence of Provincial Minimum Wage (PMW), Labor Force Participation Rate (LFPR), and Population Growth Rate (PGR) on Employment Opportunities (EO) across 20 most populous provinces in Indonesia from 2017 to 2024. Using a quantitative approach and panel data sourced from the Central Statistics Agency, the analysis applies the Fixed Effect Model selected through Chow and Hausman tests. The Outcomes indicate that PMW has a significant negative effect on EO, implying that wage increases without corresponding productivity growth can reduce job absorption. Conversely, LFPR has a significant positive effect, reflecting that a higher labor force engagement boosts employment. PGR has a negative but statistically insignificant effect. The F-test confirms that all three variables jointly influence EO. These results highlight the need to harmonize wage regulations, human capital development (HDI), and population planning to support inclusive and sustainable employment in regions experiencing high demographic pressures.